A preliminary exploration of Santa Elena's sixteenth century colonial landscape through shallow geophysics. (October 2016) - Thompson, Victor D.; DePratter, Chester B.; Thompson, Amanda D. Roberts
Abstract: Pedro Menéndez de Avilés, the founder and first governor of La Florida, established several outposts in what is now the southeastern United States. One was at the now famed city of St. Augustine (1565) and another in 1566 at the former French outpost of Charlesfort, now known as Santa Elena, marking the first Spanish occupation of the locale that would become Spain's capital in the region. In total, the colony of Santa Elena lasted for little more than two decades, as the Spanish abandoned the town in 1587. In 2014, we began a shallow geophysical survey of the site to explore its broader landscape. Given that Santa Elena is one of the best-preserved sixteenth-century towns in the United States, it presented one of the best opportunities for shallow geophysics to aid in historic sites investigations of this time period. The results of our work indicate that there is still much to be learned at the site as our ground penetrating radar, magnetic, and resistance surveys include the discovery and potential identification of structures, Spanish wells and paths, and at least one lost sixteenth century fort. Our preliminary work at Santa Elena not only demonstrates the great potential of these techniques at this site, but at historic sites in general. Highlights: Shallow geophysical surveyed revealed a number of features related to the sixteenth century Spanish occupation. GPR, resistance survey, and magnetic survey results provide information on the location of the Spanish fort of San Marcos I. Ground penetrating radar located possible Spanish period wells. Resistance survey and ground penetrating radar indicate possible buried Spanish houses in the town area of the site.